The SCL gene product is regulated by and differentially regulates cytokine responses during myeloid leukemic cell differentiation. - Tanigawa, T (1993)
Differentiation induction in murine M1 leukemia cells by interleukin 6 (IL-6), leukemia inhibitory factor (LIF), and oncostatin M (OSM) is postulated to occur via a common receptor chain, gp130. In this study, growth factor-induced differentiation of M1 cells was accompanied by a late and persistent decrease in levels of mRNA and protein for a helix-loop-helix transcription factor, the SCL gene product. To evaluate whether reduced SCL expression was instrumental in monocyte differentiation, an SCL cDNA expression vector was introduced into M1 cells to obtain cell lines in which overexpression of SCL mRNA and protein was enforced. This resulted in a reduction in cells differentiating in response to LIF and OSM but not in response to IL-6. Scatchard analysis indicated that both parental and SCL-transfected cell lines exhibited similar receptor numbers and receptor affinities for LIF, OSM, and IL-6, suggesting that the differential responsiveness was not due to selective receptor down-modulation. Thus, these data implicate SCL in monocytic differentiation and provide evidence for differential receptor signaling pathways despite utilization of a common gp130 subunit by all three receptors.